2015
DOI: 10.1002/pola.27612
|View full text |Cite
|
Sign up to set email alerts
|

Star polymers by photoinduced copper-catalyzed azide-alkyne cycloaddition click chemistry

Abstract: Well‐defined star polymers consisting of tri‐, tetra‐, or octa‐arms have been prepared via coupling‐onto strategy using photoinduced copper(I)‐catalyzed 1,3‐dipolar cycloaddition click reaction. An azide end‐functionalized polystyrene and poly(methyl methacrylate), and an alkyne end‐functionalized poly(ε‐caprolactone) as the integrating arms of the star polymers are prepared by the combination of controlled polymerization and nucleophilic substitution reactions; whereas, multifunctional cores containing either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 71 publications
0
43
0
Order By: Relevance
“…The 1 H-NMR spectra of PCL-alkyne and corresponding PP-g-PCL samples were also presented in Figure 4. As can be seen that the disappearances of characteristic alkyne and azide peaks; methine (c) 4.7 ppm and methylene (d) protons at 2.5 ppm of PCL-alkyne and methine (a) and methylene (b) as well as the appearance of triazole proton (c) at 8.12 ppm were great evidences for the successful formation of clicked product PP-g-PCL [54]. Also in Figure 5, the structure of another PPg-PEG copolymer was also analyzed by 1 H-NMR spectroscopy and the similar results were observed [45,[55][56][57][58].…”
Section: Resultsmentioning
confidence: 97%
“…The 1 H-NMR spectra of PCL-alkyne and corresponding PP-g-PCL samples were also presented in Figure 4. As can be seen that the disappearances of characteristic alkyne and azide peaks; methine (c) 4.7 ppm and methylene (d) protons at 2.5 ppm of PCL-alkyne and methine (a) and methylene (b) as well as the appearance of triazole proton (c) at 8.12 ppm were great evidences for the successful formation of clicked product PP-g-PCL [54]. Also in Figure 5, the structure of another PPg-PEG copolymer was also analyzed by 1 H-NMR spectroscopy and the similar results were observed [45,[55][56][57][58].…”
Section: Resultsmentioning
confidence: 97%
“…The radicals generated upon irradiation reduce the Cu(II) complexes to Cu(I), which mediate the click reactions. 38,[43][44][45][46][47][48][49][50][51][52] In a previous study in our laboratory, we have shown the possibility of reducing Cu(II) complexes by Type I initiators such as 2, 2-dimethoxy-2-phenyl acetophenone, 2-benzyl-2dimethylamino-4′-morpholino butyrophenone, (2,4,6 trimethylbenzoyl)diphenylphosphine oxide and dicyclopentadienyl bis[2,6-difluoro-3-(1-pyrrolyl)phenyl] titanium (titanocene) as well as camphorquinone (CQ) as Type II visible light photoinitiator. 44,53 Type I initiators directly decompose upon irradiation to yield radicals capable of reducing Cu(II) to Cu(I).…”
Section: Introductionmentioning
confidence: 99%
“…Only one synthetic approach towards peptidyl silsesquioxanes using click chemistry has been reported to date. [25][26][27][28][29][30] focussing on the synthesis of octa(3-azidopropyl)polyhedral oligomeric silsesquioxane POSS-(N 3 ) 8 ( Fig. 1) and its reaction with a variety of alkynes.…”
mentioning
confidence: 99%
“…1) and its reaction with a variety of alkynes. [25][26][27][28][29][30][31][32][33][34][35][36] The preparation of octa(3-azidopropyl)polyhedral oligomeric silsesquioxane POSS-(N 3 ) 8 requires a multi-step synthesis and suffers from a poor overall yield of 30-32%.…”
mentioning
confidence: 99%